PERLINDUNGAN HAK CIPTA MOTIF TENUN ENDEK DAN SONGKET DI DESA TELAGATAWANG - A A I Agung Maheswari; Ni Made Gitariani; Dewa Ayu Yeni Asmari; I Gede Suastika (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Weaving is one of the cultural heritage, which is the pride and identity of the Indonesian people. One of the villages where the people make the most money from weaving is Telagatawang Village, Kec. Sidemen, Karangasem. The rise of counterfeiting, piracy, due to unfair competition between employers or artisans indeed lead to conflict and losses for other parties. The issue of legal protection (Copyright) in the field of trade or business is necessary. Therefore the author will discuss "How to Process Copyright Registration and Complaints Regarding Copyright Infringement Motifs Weaving Endek and Songket." The objectives and benefits to be achieved are helping community empowerment and obtaining thought and knowledge assistance in planning and implementing development. In connection with the discussion above, we provide Weaving Counseling on Copyright Protection according to Law Number 28 of 2014 concerning Copyrights, which intended, so that weaving artisans understand related to copyright protection of their woven motifs. So that in the future, it expected that copyright registration related to weaving themes in Telagatawang Village would increase, and the craftsmen can complain and follow up on copyright-related violations such as plagiarism.